Passionate politics: Feminist theory in action - essays, 1968-1986 - Bunch, Charlotte (St. Martin's Griffin, 1987)
Essays discuss feminism, reform, lesbianism, education, the media, and the status of women around the world
Keywords: 1900-1999; amériques; approches et analyses; discipline; féminisme radical; hétérosexisme; lesbianisme; militance; mouvements des femmes*; périodes historiques; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; états-unis

Lesbians in Revolt - Bunch, Charlotte (Lesbianism and the women's movement, 1975)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; lesbianisme; militance; mouvements des femmes*; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis